Calcium current homeostasis and synaptic deficits in hippocampal neurons from Kelch-like 1 knockout mice - Perissinotti, Paula P.; Ethington, Elizabeth A.; Almazan, Erik; Martínez-Hernández, Elizabeth; Kalil, Jennifer; Koob, Michael D.; Piedras-Rentería, Erika S. (Frontiers in Cellular Neuroscience, 2015)
Kelch-like 1 (KLHL1) is a neuronal actin-binding protein that modulates voltage-gated CaV2.1 (P/Q-type) and CaV3.2 (α1H T-type) calcium channels; KLHL1 knockdown experiments (KD) cause down-regulation of both channel types and altered synaptic properties in cultured rat hippocampal neurons (Perissinotti et al., 2014). Here, we studied the effect of ablation of KLHL1 on calcium channel function and synaptic properties in cultured hippocampal neurons from KLHL1 knockout (KO) mice. Western blot data showed the P/Q-type channel α1A subunit was less abundant in KO hippocampus compared to wildtype (WT); and PQ-type calcium currents were smaller in KO neurons than WT during early days in vitro, although this decrease was compensated for at late stages by increases in L-type calcium current. In contrast, T-type currents did not change in culture. However, biophysical properties and western blot analysis revealed a differential contribution of T-type channel isoforms in the KO, with CaV3.2 α1H subunit being down-regulated and CaV3.1 α1G up-regulated. Synapsin I levels were reduced in the KO hippocampus; cultured neurons displayed a concomitant reduction in synapsin I puncta and decreased miniature excitatory postsynaptic current (mEPSC) frequency. In summary, genetic ablation of the calcium channel modulator resulted in compensatory mechanisms to maintain calcium current homeostasis in hippocampal KO neurons; however, synaptic alterations resulted in a reduction of excitatory synapse number, causing an imbalance of the excitatory-inhibitory synaptic input ratio favoring inhibition.